Cost minimization in a non-catalytic biodiesel production plant - Espinosa, Susana (2009)
In the present study, we propose an optimization model for the minimization of capital and operating costs in a supercritical methanol biodiesel plant, considering alternative process schemes together with the convenience or not to use a cosolvent in the chemical reaction. A rigorous process simulation model, based on a group contribution equation of state is integrated with a successive quadratic programming algorithm to solve the nonlinear problem. Optimization results show that noncatalytic biodiesel production with supercritical methanol can be economically competitive with conventional catalyzed production. © 2009 Elsevier B.V. All rights reserved.